Functionalized Graphene Derivatives and TiO2 for High Visible Light Photodegradation of Azo Dyes - Álvaro Pérez-Molina; Sergio Morales-Torres; Francisco J. Maldonado-Hódar; Luisa M. Pastrana-Martínez (Nanomaterials, 2020)
Functionalized graphene derivatives including graphene oxide (GO), reduced graphene oxide (rGO), and heteroatom (nitrogen/sulphur (N/S) or boron (B))-doped graphene were used to synthesize composites with TiO2 (T). The photocatalytic performance of composites was assessed for the degradation of Orange G dye (OG) under simulated solar light. All the prepared graphene derivatives—TiO2 composites showed better photocatalytic performance than bare TiO2. A higher photocatalytic activity was found for the composites containing GO and N/S co-doped rGO (kapp = 109.2 × 10−3 and 48.4 × 10−3 min−1, for GO-T and rGONS-T, respectively). The influence of both initial solution pH and the reactive species involved in the OG degradation pathway were studied. The photocatalytic activity of the samples decreased with the increase of the initial pH (from 3.0 to 10.0) due to the occurrence of electrostatic repulsive forces between the photocatalysts surface and the molecules of OG, both negatively charged. The use of selective scavengers showed that although the photogenerated holes dominate the degradation mechanism, radicals and singlet oxygen also participate in the OG degradation pathway. In addition, reutilization experiments indicated that the samples were stable under the reaction conditions used.